LDB1-mediated transcriptional complexes are sensitive to islet stress. Issue 1 (31st December 2022) - Liu, Yanping; Kepple, Jessica D.; Shalev, Anath; Hunter, Chad S.
ABSTRACT: Excess nutrients and proinflammatory cytokines impart stresses on pancreatic islet β-cells that, if unchecked, can lead to cellular dysfunction and/or death. Among these stress-induced effects is loss of key β-cell transcriptional regulator mRNA and protein levels required for β-cell function. Previously, our lab and others reported that LIM-domain complexes comprised the LDB1 transcriptional co-regulator and Islet-1 (ISL1) transcription factor are required for islet β-cell development, maturation, and function. The LDB1:ISL1 complex directly occupies and regulates key β-cell genes, including MafA, Pdx1, and Slc2a2, to maintain β-cell identity and function. Given the importance of LDB1:ISL1 complexes, we hypothesized that LDB1 and/or ISL1 levels, like other transcriptional regulators, are sensitive to β-cell nutrient and cytokine stresses, likely contributing to β-cell (dys)function under various stimuli. We tested this by treating β-cell lines or primary mouse islets with elevating glucose concentrations, palmitate, or a cytokine cocktail of IL-1β, TNFα, and IFNγ. We indeed observed that LDB1 mRNA and/or protein levels were reduced upon palmitate and cytokine (cocktail or singly) incubation. Conversely, acute high glucose treatment of β-cells did not impair LDB1 or ISL1 levels, but increased LDB1:ISL1 interactions. These observations suggest that LDB1:ISL1 complex formation is sensitive to β-cell stresses and that targeting and/or stabilizing this complex may rescue lost β-cell gene expression to preserve cellular function.